IMMIGRATION EXAMINATION IN IMMIGRATION CHECKPOINT AS AN IMPROVEMENT OF INDONESIAN'S SOCIETY WELFARE - Binsar Bonardo Sianturi; Devina Yuka Utami (Journal of Law and Border Protection, 2021)
The traffic of people in and out of the country's territory is something that cannot be stopped by any countries in the world, include Indonesia. Various factors such as economic, cultural, and social become stimulants of traffic, which then called immigration. The principle of selective policy is the principle applied in the implementation of immigration in Indonesia, which it’s implementation is carried by Directorate General of Immigration, under the Ministry of Law and Human Rights of the Republic of Indonesia. The selective policy is the basis of the implementation of immigration examination that carried out in immigration checkpoints located at airports, seaports, land border, and other immigration checkpoints, which only people who are useful and do not endanger the unity of the nation can be allowed to enter the territory of the Unitary State of Republic of Indonesia. Immigration checks are also carried out strictly on Indonesian citizens to minimize the possibility of becoming non-procedural labor which can lead to the criminal act of human trafficking. In order to increase security for achieving the welfare of the Indonesian people, the Directorate General of Immigration needs to improving the quality of its human resources which leads to advances in policy and regulation making, systems and technology, and also the technicality of immigration services.